(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The study investigates interest level of Indian children for French language in two different learning contexts, Delhi NCR, India and Quebec, Canada from the perspective of Gardner’s socio-educational model and attitude motivation test battery (AMTB). The uniqueness of the study is to compare the affective dimension of interest in learning French as an international language in Delhi NCR, India and second language, Quebec, Canada. A total of 42 in Delhi NCR and 30 in Quebec, participated in this survey study. Though, statistically, no significant difference was found in the interest level of children learning in different contexts, the responses to the survey questionnaire provided an insight on certain similarities and differences. The term interest in foreign languages, is a component of Gardner’s socio-educational model of second language acquisition and is measured by AMTB. This affective measure is part of Gardner’s composite variable “integrativeness” which was focused on learners’ orientation towards language learning in his experiments. The components according to Gardner were, “General interest in foreign groups, especially through their language, and favourable attitudes toward the target language group.”(Gardner, 2005). The paper examines the status of french language learning among Indian children. This paper will consider possible suggestions for french language professionals to reconceptualize and re-approach children’s interest to study french.